Co-culture of microalgae-activated sludge for wastewater treatment and biomass production: Exploring their role under different inoculation ratios. (October 2020) - Nguyen, Thi-Thuy-Duong; Nguyen, Thanh-Tin; An Binh, Quach; Bui, Xuan-Thanh; Ngo, Huu Hao; Vo, Hoang Nhat Phong; Andrew Lin, Kun-Yi; Vo, Thi-Dieu-Hien; Guo, Wenshan; Lin, Chitsan; Breider, Florian
Graphical abstract: Highlights: Microalgae:activated sludge ratio (3:1) was the optimum co-culture operation. Microalgae played a vital role in biomass production and nutrient removal. Under the optimum ratio, COD removal was obtained 98% in 4 days. Biological assimilation majorly contributed to nutrient removal in the co-culture PBR. Abstract: In this study, mixed culture (microalgae:activated sludge) of a photobioreactor (PBR) were investigated at different inoculation ratios (1:0, 9:1, 3:1, 1:1, 0:1 wt/wt). This work was not only to determine the optimal ratio for pollutant remediation and biomass production but also to explore the role of microorganisms in the co-culture system. The results showed high total biomass concentrations were obtained from 1:0 and 3:1 ratio being values of 1.06, 1.12 g L -1, respectively. Microalgae played a dominant role in nitrogen removal via biological assimilation while activated sludge was responsible for improving COD removal. Compared with the single culture of microalgae, the symbiosis between microalgae and bacteria occurred at 3:1 and 1:1 ratio facilitated a higher COD removal by 37.5–45.7 %. In general, combined assessment based on treatment performance and biomass productivity facilitated to select an optimal ratio of 3:1 for the operation of the co-culture PBR.